Correlation of endoscopic ultrasound-guided portal pressure gradient measurements with hepatic venous pressure gradient: a prospective study - Martinez-Moreno, Belén; Martínez Martínez, Juan; Herrera, Iván; Guilabert, Lucía; Rodríguez-Soler, María; Bellot, Pablo; Miralles, Cayetano; Pascual, Sonia; Irúrzun, Javier; Zapater, Pedro; Palazón-Azorín, José María; Gil Guillén, Vicente; Jover, Rodrigo; Aparicio, José R. (Endoscopy, 2024)
Background Hepatic venous portal gradient (HVPG) measurement remains the gold standard for estimating portal pressure gradient (PPG). This study aimed to evaluate the correlation between endoscopic ultrasound (EUS)-guided PPG and HVPG in patients with chronic portal hypertension.Methods Patients with chronic portal hypertension in whom HVPG assessment was clinically indicated were invited to undergo transjugular HVPG and EUS-PPG with a 22-G needle in separate sessions for comparison. Intraclass correlation coefficient (ICC) and the Bland–Altman method were used to evaluate the agreement between techniques.Results 33 patients were included. No significant differences in technical success were observed: EUS-PPG (31/33, 93.9%) vs. HVPG (31/33, 93.9%). Overall, 30 patients who underwent successful EUS-PPG and HVPG were analyzed. Correlation between the two techniques showed an ICC of 0.82 (0.65–0.91). Four patients had major discrepancies (≥5 mmHg) between HVPG and EUS-PPG. No significant differences in adverse events were observed.Conclusions The correlation between EUS-PPG and HVPG was almost perfect. EUS-PPG could be a safe and reliable method for direct PPG measurement in patients with cirrhosis and a valid alternative to HVPG.